Descriptive aroma profiles of fresh sweet basil cultivars (Ocimum spp.): Relationship to volatile chemical composition. Issue 7 (23rd June 2021) - Patel, Meera; Lee, Rachel; Merchant, Emily V.; Juliani, H. Rodolfo; Simon, Jame E.; Tepper, Beverly J.
Abstract : Abstract: Few studies have linked sensory descriptions of the aroma profiles of fresh, sweet basil varieties with their volatile chemistry. Using a recently developed lexicon for fresh basil, a descriptive panel characterized the aroma profiles of seven basil varieties. Chemical analysis of fresh basil leaves was performed using GC‐MS headspace analysis. Analysis of variance probed for differences in the sensory attributes among varieties and principal component analysis (PCA) related the sensory profiles to volatile chemical composition. Three commercial specialty basils, "Queenette Thai" (QT), "Sweet‐Dani" (SD) lemon basil, and MC‐9 (cinnamon basil) had strong anise, lemon, and cinnamon‐like aromas, respectively. These basils were distinguished from breeding lines of traditional Italian sweet basils where SB‐22, CB‐1, and CB‐39 exhibited strong anise‐like aroma and SB‐17 had strong "general spice" aromas, characteristic of a warm spice blend. The PCA accounted for 58.7% of the variation in the data and characterized the samples in two dimensions: general spice—citrus and cinnamon‐like—anise. There was a strong correspondence between the sensory attributes and volatile chemical composition. SD associated with lemon aroma and citral content; QT, CB‐1, and CB‐39 associated with anise aroma and methyl chavicol; and MC‐9 associated with the cinnamon‐like aroma, methyl cinnamate. SB‐17 and SB‐22 associated with general spice aroma and were in close proximity to the spice‐like volatiles, 1, 8 cineole, and eugenol, associated with clove aroma. We constructed precise sensory/chemical profiles for fresh basil aroma that can be used to guide breeding programs for variety improvement to meet consumer expectations or market demand. Practical Application: Sweet basil aroma is due to a complex array of several aromatic volatile compounds. The presence, concentration, and the particular ratios in which these aroma compounds accumulate significantly impact the sensory attributes. Understanding aroma profiles for fresh basil have practical applications in product development, procurement, food preparation, ethnic cuisine, and processing. Plant genetics and breeding of aroma profiles can be used and incorporated in plant improvement programs.